"Totally unacceptable" : representations of homosexuality in South African public discourse - Mutambanengwe, Simbarashe Abel (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
The 1996 Constitution of South Africa is ranked as one of the most liberal and democratic constitutions in the world. The right to freedom of sexual orientation, equality and the freedom of association amongst other rights is in its Bill of Rights and are thus inherently assured and protected in post- apartheid, democratic South Africa. However, the Lesbian Gay Bisexual and Transgender (LGBT) community continue to face discrimination and prejudice despite this newly established constitutional order. The present study is interested in how, in the light of the equality clause in the South African constitution, homosexuality is represented and constructed in the South African media. The thesis examines representations of homosexuality between the years 1999-2013 in articles collected from the Independent Online media site which incorporates 30 newspapers. The approach focuses on the topics, overall news report schemata, local meanings, style and rhetoric of the news reports. The results of the study show that negative attitudes towards homosexuality are framed in three main ways: homosexuality is represented as "unAfrican"; "ungodly" and "unnatural". I argue that rather than extreme forms of violence (such as "corrective rape" and murder) directed against LGBT citizens being interpreted as the aberrant behaviour of a few, these need to be understood in the context of the circulation of the above justificatory narratives.
Keywords: Independent Online; Homosexuality -- South Africa; Sexual minorities in mass media -- South Africa; Mass media and gays -- South Africa; Homophobia -- Press coverage -- South Africa; Electronic newspapers -- South Africa